Pemanfaatan Pohon Kelapa dalam Meningkatkan Perekonomian Masyarakat Desa Mekar Laras - Salsabila Salsabila; Wasiyem Wasiyem; Siti Nurhaliza Fardani; Vira Zul Fahny; Putri Aulia Rahma (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Economic development in the village of Mekar Laras today not only focuses on the modern sector and industrialization but also emphasizes the importance of utilizing sustainable local potentials, one of which is the local wisdom in managing coconut tree resources. This study aims to describe the utilization of coconut trees as local wisdom that plays a role in improving the economy of the Mekar Laras community. The research method used is qualitative with a descriptive approach, involving five informants consisting of community leaders, coconut entrepreneurs, and the general public. Data collection techniques were conducted through in-depth interviews and documentation, which were then analyzed using a thematic approach. The results of the study show that almost all parts of the coconut tree can be optimally utilized, including the fruit, leaves, trunk, and husk. The coconut fruit is processed into coconut milk, oil, jelly, and nata de coco, while the husk and coconut shells are used as fuel, crafts, and eco-friendly briquettes. These processed products are not only used for household needs and traditional ceremonies but also marketed outside the region and exported to neighboring countries. This indicates that coconut plays a strategic role in supporting the community's economy and preserving local culture. The challenges faced include limited technology, aging coconut trees, and minimal government support. Therefore, strategies for developing coconut-based businesses through technological innovation, digital marketing, and strengthening farmer group institutions are essential.